Expedição brasileira à Antártica: a aclimatização ao calor, observada durante um exercício físico em ambiente quente após o retorno ao Brasil, ocorre em concomitância com o aumento da tolerância ao frio nas mãos - Ygor Antônio Tinoco Martins (2020)
The main challenges for the human organism of individuals moving to Antarctica are the maintenance of internal body temperature and the defense of the body's extremities from injuries by the cold. The use of specific clothing for the cold is a thermoregulatory behavior to guarantee physical integrity, as these are capable of generating a hot microclimate, due to the insulating characteristics. However, the warm microclimate provided by the clothes, associated with the increase in metabolic heat production during activities in the field in Antarctica that depend on physical effort, result in an increase in internal temperature and the consequent physiological responses to heat. Considering the possible effect of the Antarctic environment on thermoregulation, the objective of the study was to assess, in a group of Brazilian researchers, whether staying in a camp in Antarctica results in acclimatization to heat and to whether to assess this response would occur in conjunction with peripheral cold adaptations. The sample of this study was composed of seven volunteers (5 women and 2 men), who went through three experimental situations: “Pré-Antarctica” held in Brazil 27 days before the trip to start the expedition, “Antarctica” in which they were data were collected within the 32-day camp in Antarctica, and “Post-Antarctic” held in Brazil 18 days after the completion of the camp. In the “Pre-Antarctic” and “Post-Antarctic” experimental situations, the same experimental procedures were performed, divided into two days of data collection, with a 48- hour interval between them. On the first experimental day, the volunteers' physical characteristics assessed were and a test performed was to measure the maximum oxygen consumption (V̊ O2MÁX). On the second day of data collection, a submaximal physical exercise (60%Vmáx) performed was in a warm environment (31oC and 60% URA) and the evaluation of the tolerance of hand exposure to water at 2o C. In the “Antarctic” situation, the internal body temperature evaluated was movement over a typical field day and evaluation of the tolerance of hand exposure to water at 2° C. After returning from the Antarctic expedition, the volunteers showed an increase in the total exercise time during the test to evaluate the V̊ O2MÁX; however, there was no difference in V̊ O2MÁX. During submaximal exercise in the “Post-Antarctic” situation, we observed an increase in the the rate of local sweating on the forehead, and the number of active sweat glands on the forehead, as well as reducing in the skin temperatures of the forehead and chest. Regarding the tolerance of hand exposure to cold, the volunteers showed a reduction in the cooling rate and a tendency to increase the tolerance to water at 2° C in the “Antarctic” situation. Staying in a camp in Antarctica for 32 days was enough to elicit lasting adaptive physiological responses to heat, resulting in improved physical performance as a result of physical exertion in the field and leading to increased tolerance in a peripheral region (hand) to cold, however the latter was not maintained 18 days after the end of the expedition.